Komunikasi Interpersonal Pasangan Suami Istri Dalam Upaya Menjaga Keharmonisan Rumah Tangga - Mia Nurislamiah (Communicative : Jurnal Dakwah dan Komunikasi, 2021)
The purpose of this study is to determine the process of interpersonal communication, interpersonal communication barriers, and the quality of interpersonal communication between husband and wife in an effort to maintain household harmony. This study uses qualitative methods with data collection techniques used include: observation, in-depth interviews, and documentation studies. The data analysis technique used in this study is a qualitative descriptive analysis technique. Meanwhile, the validity of the data was checked using the source triangulation technique, using reference materials and member check techniques. The results of this study indicate that in general, informants have a communication process that is characterized by exchanging information, always limiting the topics they want to talk about, and revealing something they don't like from their partner for good. Communication barriers to informants consist of physical, psychological, and conflict barriers. The quality of informant communication consists of openness, empathy, supportive attitude, positive attitude, honesty, and equality. However, the third and fourth informants did not have a supportive attitude aspect.